2020
DOI: 10.1186/s12886-020-01335-x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of vitreo-retinal diseases at the national referral hospital in Bhutan: a retrospective, hospital-based study

Abstract: Background: Knowing the pattern and presentation of the diseases is critical for management strategies. To inform eye-care policy we quantified the pattern of vitreo-retinal (VR) diseases presenting at the national referral hospital in Bhutan. Methods: We reviewed all new patients over three years from the retinal clinic of the Jigme Dorji Wangchuck National Referral Hospital. Demographic data, presenting complaints and duration, treatment history, associated systemic diseases, diagnostic procedures performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…Our study of the pattern and presentation of VR diseases in Bhutan [10] and a similar study in Nepal [23] reported that the majority of patients were males (60.3 and 53.0% respectively). That trend was followed here for patients receiving RLT, 60.0% of whom were males.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Our study of the pattern and presentation of VR diseases in Bhutan [10] and a similar study in Nepal [23] reported that the majority of patients were males (60.3 and 53.0% respectively). That trend was followed here for patients receiving RLT, 60.0% of whom were males.…”
Section: Discussionsupporting
confidence: 62%
“…PRP was the most common RLT performed in our study because VR diseases requiring PRP such as DR and CRVO were very common in Bhutan [10], and in Nepal too [23]. Similarly, modified grid laser was the second most common laser procedure performed because DR and DMO were common [10]. RLT is still the most common and standard treatment for DR and DMO in developing countries for economic reasons [37].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations